Effectivity of imatinib therapy for the management of chronic myeloid leukemia patients (Bangladesh Medical Journal Khulna, 2019)
Background: First generation tyrosine kinase inhibitor, imatinib revolutionized the treatment of chronic myeloid leukaemia, and is now the front line therapy. Imatinib provides substantial cytogenetic and molecular remission, with minimal normal hematopoiesis suppression or side effects and is now first line therapy.Objective: The aim of this prospective study was to determine the efficacy of imatinib therapy in the management of chronic myeloid leukemia in Bangladesh.Methods: This prospective study was done from June 2012 to May 2018. In this period we treated eight chronic myeloid leukaemia patients with imatinib, in Khulna division, Bangladesh.Results: Majority of the patients (50%) were in the age group of 21-30 years. Three patients died as because those patients were too poor to continue drugs. Another 5 patients were in good health and continuing follow up monthly. Among five patients, one patient have two healthy son.Conclusion: Imatinib therapy is an effective treatment regimen in the management of chronic myeloid leukaemia. The best result can be obtained if CML is dignosed earlier.Bang Med J (Khulna) 2018; 51 : 40-43